Intrageneric cross-reactivity of monospecific rabbit antisera against venoms of the medically most important Bitis spp. and Echis spp. African snakes - Gómez Argüello, Aarón (2022)
Snakebite envenomation exerts a heavy toll in sub-Saharan Africa. Antivenom is the only valid therapy for these envenomations. However, owing to the wide variety of snake species and the large variation in venom composition, the selection of the best combination of venoms to generate effective polyclonal antivenoms of wider neutralizing coverage is challenging. In this study, an experimental protocol was developed based on the generation of monospecific antisera in rabbits immunized with venoms of Bitis spp. or Echis spp. from Africa. Cross-reactivity of monospecific antisera was assessed by immunochemical analyses and by neutralization of toxic effects. Results revealed a large extent of intrageneric cross-reactivity by all antisera, with few exceptions. The venoms that generated antisera with the highest cross-reactivity and neutralizing ability among Bitis spp. were those of Bitis gabonica and B. rhinoceros, and of Echis leucogaster in Echis spp. These results provide evidence for the selection of the best combination of venoms for preparing antivenoms of high neutralizing scope within these two medically relevant genera of African viperid species. These results in rabbits must be translated to large animals used in antivenom production to assess whether these predictions are confirmed.